2023
DOI: 10.1038/s41368-023-00224-5
|View full text |Cite
|
Sign up to set email alerts
|

Autologous mesenchymal stem cells offer a new paradigm for salivary gland regeneration

Abstract: Salivary gland (SG) dysfunction, due to radiotherapy, disease, or aging, is a clinical manifestation that has the potential to cause severe oral and/or systemic diseases and compromise quality of life. Currently, the standard-of-care for this condition remains palliative. A variety of approaches have been employed to restore saliva production, but they have largely failed due to damage to both secretory cells and the extracellular matrix (niche). Transplantation of allogeneic cells from healthy donors has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 233 publications
1
9
0
Order By: Relevance
“…In addition, we found that the ACC and MECA samples had a higher proportion of stem cells and myoepithelial cells (Wilcoxon Rank Sum p -value < 0.001), whereas the SDC and MEC samples exhibited abundant fibroblasts, dendritic cells (DCs), and ductal/basal epithelial cells (Wilcoxon Rank Sum p -value < 0.001). These results are consistent with the known cellular compositions of ID (higher rate of cellular division and stem cell properties) and ED (higher number of professional antigen-presenting cells (APCs)) 30 34 .
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…In addition, we found that the ACC and MECA samples had a higher proportion of stem cells and myoepithelial cells (Wilcoxon Rank Sum p -value < 0.001), whereas the SDC and MEC samples exhibited abundant fibroblasts, dendritic cells (DCs), and ductal/basal epithelial cells (Wilcoxon Rank Sum p -value < 0.001). These results are consistent with the known cellular compositions of ID (higher rate of cellular division and stem cell properties) and ED (higher number of professional antigen-presenting cells (APCs)) 30 34 .
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…The final goal of differentiating SG cells is to provide a cure for xerostomia patients. There have been clinical trials of allogeneic MSC transplantation, but they showed only short-term effect and could not repair damaged cells in the long term [6]. A possible reason would be immune rejection of MSC [25].…”
Section: Application and Limitationmentioning
confidence: 99%
“…Stem cell-based approaches hold great promise for SG regeneration due to their unique ability to differentiate into various cell types and promote tissue repair. Previous animal studies on engrafting mesenchymal stromal cells (MSCs) into damaged SG showed increased salivary flow rate and SG mass [6]. Meanwhile, Lin et al (2011) [7] have shown a more desirable effect using MSC-derived acinar-like cells for treatment compared to using MSC directly.…”
Section: Introductionmentioning
confidence: 99%
“…This groundbreaking work marks the first instance of salivary gland rescue using salispheres and the first clear demonstration of salivary gland stem/progenitor cell self-renewal and multilineage differentiation into functional organoids. MSCs are multipotent adult stem cells that can differentiate into several cell types, including adipocytes [184], osteoblasts [185], chondrocytes [186], myocytes [187], cardiomyocytes [188], hepatocytes [189], neuronal cells [190], and salivary gland cells [191], among others. MSCs exhibit anti-inflammatory, anti-fibrotic, and regenerative potential [192,193].…”
Section: Salivary Gland Stem Cells (Sgscs)mentioning
confidence: 99%